2020
DOI: 10.1186/s13256-020-02512-8
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal effect in pulmonary carcinoid tumor following ablative stereotactic body radiation therapy: a case report

Abstract: Background The abscopal effect was described as early as the 1950s, when untreated tumors demonstrated a response after radiation therapy was delivered to an untreated, distant site. The mechanisms underlying this global response to otherwise localized therapy remain unknown, though there is increasing evidence that increased antigen expression following ablative radiotherapy may play a role. Case presentation We report a case of a 69-year-old African American woman with a history of metastatic typical pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, immunotherapy compensates for this rarity. Multiple clinical and pre-clinical studies (Table I) have shown that, compared with the effect of radiotherapy or immunotherapy alone, the combination of radiotherapy and immunotherapy can significantly increase the incidence and intensity of the abscopal effect (7,13,(163)(164)(165)(166). Commonly used immune checkpoint inhibitors are anti-CTLA-4, anti-PD-1 and anti-PD-L1 antibodies, all of which strengthen the effect of T cells on tumor cells and can be combined with radiotherapy to enhance the incidence rate of the abscopal effect.…”
Section: Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunotherapy compensates for this rarity. Multiple clinical and pre-clinical studies (Table I) have shown that, compared with the effect of radiotherapy or immunotherapy alone, the combination of radiotherapy and immunotherapy can significantly increase the incidence and intensity of the abscopal effect (7,13,(163)(164)(165)(166). Commonly used immune checkpoint inhibitors are anti-CTLA-4, anti-PD-1 and anti-PD-L1 antibodies, all of which strengthen the effect of T cells on tumor cells and can be combined with radiotherapy to enhance the incidence rate of the abscopal effect.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Compared with traditional radiotherapy methods, new technologies may be more conducive to the generation of the abscopal effect. Stereotactic body radiation therapy combined with immunotherapy is well tolerated and relatively safe, and there were cases of lung cancer as well as head and neck squamous cell carcinoma where the abscopal effect was generated by such a combination ( 163 , 166 ). In addition, technologies such as intensity-modulated radiation therapy, stereotactic ablative radiotherapy or proton therapy can change the range of radiotherapy according to the tumor size and greatly reduce radiation toxicity ( 3 ), thus overcoming the toxicity caused by combined therapy.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…An interesting issue that was described by Kareff et al is to obtain an abscopal effect in a patient with typical lung carcinoid [ 69 ]. The abscopal effect is the regression of the disease beyond the irradiation area.…”
Section: The Role Of Radiotherapy In the Treatment Of Tc And At Carcinoidsmentioning
confidence: 99%
“…The lesion not irradiated with the same lung decreased from 1.5 cm to 0.5 cm in the greatest dimension. The third nodule in the opposite lung showed dimensional stabilization [ 69 ]. Searching the pub-med database, a second case was found that described the achievement of the abscopal effect in a patient with atypical carcinoid tumor.…”
Section: The Role Of Radiotherapy In the Treatment Of Tc And At Carcinoidsmentioning
confidence: 99%
“…Notably, despite the increasing use of hypo-fractionated or stereotactic ablative RT, known to improve IR’s ability to promote immune responses to tumors [ 4 ], AE has remained a rare phenomenon for a long time, with only 46 cases reported up to 2014 [ 5 ]. However, the introduction of immune checkpoint inhibitors (ICIs), shown to boost the RT-induced immune response [ 6 , 7 ] and to be potentiated by RT [ 8 ], has drastically increased the number of cases reporting AE [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , …”
Section: Introductionmentioning
confidence: 99%